Endothelial GATA4 controls liver fibrosis and regeneration by preventing a pathogenic switch in angiocrine signaling - Winkler, Manuel; Staniczek, Theresa; Kürschner, Sina Wietje; Schmid, Christian David; Schönhaber, Hiltrud; Cordero, Julio; Kessler, Linda; Mathes, Arthur; Sticht, Carsten; Neßling, Michelle; Uvarovskii, Alexey; Anders, Simon; et al. (Journal of hepatology, 2021)
Background and Aims - Angiocrine signaling by liver sinusoidal endothelial cells (LSEC) regulates liver functions such as liver growth, metabolic maturation, and regeneration. Recently, we identified GATA4 as the master regulator of LSEC specification during development. Here, we studied endothelial GATA4 in the adult liver and in hepatic disease pathogenesis. - Methods - We generated adult Clec4g-icretg/0xGata4fl/fl (Gata4LSEC-KO) mice with deficiency of Gata4 in LSEC. Livers were analyzed by histology, electron microscopy, immunohistochemistry/immunofluorescence, in-situ hybridization, and by expression profiling, ChIP- and ATAC-sequencing of isolated LSEC. For liver regeneration, partial hepatectomy was performed. As models of liver fibrosis, CDAA diet and chronic CCl4 exposure were applied. Human single cell RNAseq data sets were analyzed for endothelial alterations in healthy and cirrhotic livers. - Results - Genetic Gata4 deficiency in LSEC of adult mice caused perisinusoidal liver fibrosis, hepatopathy and impaired liver regeneration. Sinusoidal capillarization and LSEC-to-continuous endothelial transdifferentiation were accompanied by a profibrotic angiocrine switch including de novo endothelial expression of hepatic stellate cell-activating cytokine Pdgfb. Increased chromatin accessibility and amplification by activated MYC mediated angiocrine Pdgfb expression. In CDAA diet-induced perisinusoidal liver fibrosis, LSEC showed repression of GATA4, activation of MYC and the profibrotic angiocrine switch already detected in Gata4LSEC-KO mice. Comparison of CDAA-fed Gata4LSEC-KO and control mice demonstrated that endothelial GATA4 indeed protects from dietary-induced perisinusoidal liver fibrosis. In human cirrhotic livers, GATA4-positive LSEC and endothelial GATA4 target genes were reduced, while non-LSEC endothelial cells and MYC target genes including PDGFB were enriched. - Conclusions - Endothelial GATA4 protects from perisinusoidal liver fibrosis by repressing MYC activation and profibrotic angiocrine signaling on the chromatin level. Therapies targeting the GATA4/MYC/PDGFB/PDGFRβ axis offer a promising strategy for prevention and treatment of liver fibrosis.